SMS Information Display Board - A. Tanadumrongpattana; A. Suethakorn; S. Mitatha; C. Vongchumyen (My University, 2011)
We propose a new system for SMS information display board. The system will display texts and icons of a message on the matrix LED. To sending a message to the system, A user have to send a message SMS on a mobile phone. It's mean, the user can be anywhere in the range of mobile signal to control the message on the display board. Furthermore, the user is able to control the pattern, speed and time duration of the display message. In additional, the user can set the time of the message to display on the system in advance or cancel it. The system provide the security by using password method to verified the authorize user only. Finally the system can apply to variety of usage with a lot of concurrent users and message scheduling application.
Keywords: Mobile phone; Bluetooth and Wireless Communication Technologies